Development of Contextual Based Science Module - Ovilia Putri Utami Gumay; Ivoni Susanti; Wahyu Arini (Jurnal Penelitian Pendidikan IPA, 2025)
The problem in learning science at SMP N Air Satan is the low involvement of students actively due to the use of conventional methods and limited learning resources. This study aims to develop a contextual-based science module that is valid, practical, and effective to improve students' concept understanding. The method used was Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate), but limited to the first three stages. Data were collected through validation questionnaires (by material, language, and media experts), student practicality questionnaires, and learning outcome tests. The data were analyzed quantitatively descriptively to measure the validity, practicality, and effectiveness of the product. The validation results showed that the module was in the “valid” category, with a material expert validation score of 45, media expert 43, and linguist 27. Student responses to the practicality of the module reached 80.69% (“practical” category), and student learning outcomes showed learning completeness of 77.26%, exceeding the KKM 72. Thus, the contextual-based science module developed has proven to be valid, practical, and effective for use in the science learning process in junior high school.